Produktivitas Kambing Perah Peranakan Ettawa (PE) pada Tingkat Kelompok Tani Ternak di Lombok Tengah (Studi Kasus Pada Kelompok Tani Ternak) - Kertanegara Kertanegara; Muhammad Dohi; I Nym. Sadia; A. Rai; S. Asih; Suhubdy Yasin (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
This study aims to determine the productivity of PE goats kept by Livestock Farmers Groups in Central Lombok Regency. This study used a survey method with the determination of sample villages based on the presence of PE goat Livestock Farmers Groups in KTT and PE goats as respondents were determined by census and taken as respondents. This research was carried out at two locations, namely the Livestock Farmers Group and the Animal Feed and Nutrition Laboratory, Faculty of Animal Husbandry, Unram. The variables measured were the amount and type of feed given, milk production, fat and milk protein content of each lactating PE goat, belonging to members of the Livestock Farming Group. The research data will be tabulated and analyzed using the Arithmatic Mean and Standard Deviation using the MS Excel 2007 spreadsheet, then discussed descriptively. The results of the study were 6 target summits with 49 active members and all of them were part time jobs with a population of 107 PE goats, consisting of 23 males and 84 females of various ages. And the composition of the forage consisted of 4 types of grass or around 26.67%, 4 types of leguminous or around 26.67% and 7 types of trees or around 46.67%, from the 107 PE goats, 16 males or about 66 of them obtained feed status. .67% was sufficient and 8 heads or around 33.33% were not sufficient and as many as 29 females or around 34.94% were sufficient and as many as 54 heads or around 65.06% the feed requirement was not fulfilled. The average milk production of 16 lactating PE goats belonging to members of the target summit was around 306.10 ± 221.96 ml/head/day, which was relatively low, with a fat content of 3.4037 ± 0.6579%, which was quite good, still meeting SNI milk quality standards ( 3.0%) and the Directorate General of Labor (≥ 2.8%), while the protein content of 3.7837 ± 0.5127% is quite high, still meeting SNI standards (2.8%) and the Directorate General of Labor (≥ 2.7%).